BLOOD PARASITES MORPHOTYPES OF ROCK LIZARDS OF ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In the paper morphological characteristics of blood parasites of 8 species of rock lizards of Darevskia genus were investigated. Their prevalence in the host organism was revealed.
Keywords: rock lizards, blood parasite, morphotype, gametogenesis, Karyolysus, Hepatozoon